How costly are public sector inefficiencies? A theoretical framework for rationalising fiscal consolidations - Jorge Onrubia-Fernández; Antonio Jesús Fuentes (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
Fiscal adjustments consisting of spending cuts or tax increases are generally presented as the unavoidable way for achieving public finance sustainability in the long term. However, this view of fiscal consolidation processes is limited as it leaves out other aspects related to public sector performance which are relevant not only from the macroeconomic but also from the microeconomic perspective. This paper models Public Sector Performance (PSP) by proposing a theoretical framework that integrates the conventional methodology for measuring its productive efficiency and the monetary assessment of social welfare changes linked to public policy reforms. Two equivalent measures of social welfare change generated by improving (or worsening) productive efficiency are deduced using duality theory. The first is obtained from the cost function, while the second arises directly from the production function. The results reveal that taking advantage of budgetary savings obtained from this approach constitutes a valuable tool for designing welfare-enhancing fiscal consolidation packages, meanwhile promoting sound fiscal balances and growth prospects over the long term.
Keywords: D24; D60; D61; H40; H50; 330; public sector efficiency; technical efficiency; allocative efficiency; social welfare changes